How social media platforms earn revenues for telecommunication companies - a perspective from X Solutions Limited - Ador, Fahim Shahriar (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.